Hubungan Antara Father Involvement dalam Pengasuhan dengan Preferensi Pemilihan Pasangan pada Perempuan Dewasa Awal - Alya Shalsabilla Juliyanti; Yuarini Wahyu Pertiwi; Wahyu Aulizalsini Alurmei (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Partner selection preferences are an important aspect of early adulthood because they are related to the formation of healthy and lasting romantic relationships. One factor believed to be associated with the development of these preferences is a father’s involvement in child-rearing. This study aims to examine the relationship between a father’s involvement and partner selection preferences among young adult women. The study employed a quantitative approach with a correlational design. The sample consisted of 113 young adult women aged 18–30 years, recruited using non-probability sampling techniques. Hypothesis testing results indicated a significant positive relationship between father involvement and partner selection preferences among young adult women (r = 0.2999; p = 0.001). These findings suggest that the higher a father’s involvement in child-rearing, the higher the partner selection preferences of young adult women. However, the strength of the relationship was relatively low, indicating that partner selection preferences are also influenced by factors other than father involvement. This study implies that father involvement plays a role in shaping healthy and realistic partner standards among young adult women.